2016
DOI: 10.1021/acs.jpcc.6b02538
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Carbon Nanotube Defects Manifest Substantial Vibrational Reorganization

Abstract: Fluorescent defects have opened up exciting new opportunities to chemically tailor semiconducting carbon nanotubes for imaging, sensing, and photonics needs such as lasing, single photon emission, and photon upconversion. However, experimental measurements on the trap depths of these defects show a puzzling energy mismatch between the optical gap (difference in emission energies between the native exciton and defect trap states) and the thermal detrapping energy determined by application of the van 't Hoff equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(133 citation statements)
references
References 40 publications
15
114
0
Order By: Relevance
“…Reactions were carried out at bulk solution temperatures ranging from 23 to 50 °C and monitored spectroscopically ( Figure 4 b). It should be noted that although we recognize that PL measurements of SWCNT vary with temperature, 7 we only monitor the change in defect PL intensity for our evaluation here. The temporal evolutions of defect PL at various temperatures fit well per first order reaction kinetics.…”
mentioning
confidence: 99%
“…Reactions were carried out at bulk solution temperatures ranging from 23 to 50 °C and monitored spectroscopically ( Figure 4 b). It should be noted that although we recognize that PL measurements of SWCNT vary with temperature, 7 we only monitor the change in defect PL intensity for our evaluation here. The temporal evolutions of defect PL at various temperatures fit well per first order reaction kinetics.…”
mentioning
confidence: 99%
“…During their effective lifetime they can move about 100 nm along the nanotube. [169][170][171] With this method a substantial increase in emission efficiency can be achieved. This means that short nanotubes will exhibit much lower photoluminescence yields than longer nanotubes with a saturation at lengths above 1 µm in dispersion.…”
Section: Exciton Transfer and Diffusionmentioning
confidence: 99%
“…This means that short nanotubes will exhibit much lower photoluminescence yields than longer nanotubes with a saturation at lengths above 1 µm in dispersion . This contribution to the overall low photoluminescence of SWCNTs can be circumvented by introducing luminescent sp 3 ‐defects that localize the exciton and enable radiative decay even for very short nanotubes although at lower energies . With this method a substantial increase in emission efficiency can be achieved.…”
Section: Optical and Electronic Propertiesmentioning
confidence: 99%
“…Some studies have reported that several photoluminescence features (such as emission energy and maximum brightness) can be chemically tuned using withdrawing/donating substituents on the aryl functional group. 16,17 It has even been shown that SWCNTs can be photoexcited to induce an acceleration in diazonium functionalization. 18 Even if the intended alteration of the SWCNTs' electronic structure is a fact, by means of diazonium chemistry or any other approach, on many occasions there is a need to unravel the nature of doping (negative, n-or positive, p-) and its extension.…”
Section: Introductionmentioning
confidence: 99%